Pendidikan Anak Dalam Perspektif Hadits Nabawi - Muhammad Hambal Shafwan (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
This article discusses the concepts and principles of child education derived from the teachings of the Prophet Muhammad (peace be upon him) through his hadiths. This study emphasizes that child education in Islam does not only focus on intellectual aspects, but also encompasses the development of morals, spirituality, and personality as a whole. The method used is a literature review by analyzing various hadiths related to parenting and child education. The results of the study indicate that the Prophet Muhammad (peace be upon him) emphasized the importance of compassion, role models, habituating worship, and instilling moral values ​​from an early age. Furthermore, the role of parents as primary educators is strongly emphasized in shaping children's character. This article concludes that child education from the perspective of the Prophetic hadith is holistic and relevant for application in the context of modern education to shape a generation with faith, noble morals, and strong personalities.